SUBCLINICAL LEFT VENTRICULAR DYSFUNCTION IN PATIENTS WITH ISOLATED SEVERE RHEUMATIC MITRAL STENOSIS HAVING NORMAL LEFT VENTRICULAR EJECTION FRACTION - Abbasi, Waleed Ahmed; khan, Hamid Sharif; Nazeer, Atif; Saleem, Muhammad (Journal of Ayub Medical College Abbottabad, 2020)
Background: Mitral stenosis (MS) is a prevalent disease in the developing world. It is a preventable disease associated with considerably high morbidity and mortality rates. Myocarditis secondary to rheumatic MS can cause left ventricular (LV) dysfunction. In majority of the case this LV dysfunction is subclinical. Recent development in imaging techniques like tissue Doppler imaging (TDI) and strain imaging enabled us to detect subclinical LV dysfunction. One such example is Global Longitudinal Strain (GLS), which is a reliable mean of assessing LV dysfunction in patients diagnosed with mitral stenosis. Objective of the study was to determine frequency of subclinical LV dysfunction by mean GLS in patients with isolated severe Rheumatic MS having normal LV Ejection fraction measured by 2D/M-mode echocardiography. Methods: It was an observational cross-sectional study, conducted at Department of Cardiology, Rawalpindi Institute of Cardiology, Rawalpindi, during the period of six months from 1st January to 30th June 2016. Fifty-five patients with isolated severe mitral stenosis of underlying rheumatic aetiology with preserve LV function (EF>50%) were selected as per other inclusion and exclusion criteria. All patients were evaluated with detailed history, physical examination and echocardiographic examination. GLS was also noted and all other information was recorded on data collection form. Results: The average age and mean GLS was 48.20±11.62 years and -19.24±1.15% respectively. Left ventricular systolic impairment in patients under study using the Global Longitudinal Strain was seen in 16.36% (9/55) cases. Conclusion: Our results suggest that GLS helps in detecting impairment of LV systolic function at an early stage in patients with mitral stenosis which helps in their risk stratification thus warranting their early management Keywords: Mitral stenosis; Subclinical LV dysfunction; GLS; Severe Rheumatic